Isolation of Human Islets for Autologous Islet Transplantation in Children and Adolescents with Chronic Pancreatitis. (8th February 2012) - Bottino, Rita; Bertera, Suzanne; Grupillo, Maria; Melvin, Patricia R.; Humar, Abhinav; Mazariegos, George; Moser, A. James; Walsh, R. Matthew; Fung, John; Gelrud, Andres; Slivka, Adam; Soltys, Kyle; et al.
Abstract : Chronic pancreatitis is an inflammatory disease of the pancreas that causes permanent changes in the function and structure of the pancreas. It is most commonly a complication of cystic fibrosis or due to a genetic predisposition. Chronic pancreatitis generally presents symptomatically as recurrent abdominal pain, which becomes persistent over time. The pain eventually becomes disabling. Once specific medical treatments and endoscopic interventions are no longer efficacious, total pancreatectomy is the alternative of choice for helping the patient achieve pain control. While daily administrations of digestive enzymes cannot be avoided, insulin-dependent diabetes can be prevented by transplanting the isolated pancreatic islets back to the patient. The greater the number of islets infused, the greater the chance to prevent or at least control the effects of surgical diabetes. We present here a technical approach for the isolation and preservation of the islets proven to be efficient to obtain high numbers of islets, favoring the successful treatment of young patients.